1984
DOI: 10.1128/iai.46.2.559-563.1984
|View full text |Cite
|
Sign up to set email alerts
|

Activation of complement system by porins extracted from Salmonella typhimurium

Abstract: The effect of porins purified from Salmonella typhimurium on the complement system was investigated both in vitro and in vivo. Incubation of porins with either human or guinea pig serum resulted in the consumption of the total complement activity when an amount of porins ranging from 8 to 10 ,ug per 100 ,ld of serum was used. The activation of the complement system was temperature dependent, suggesting an active process rather than passive adsorption of the complement components by porins. In addition, the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…This evidence of proinflammatory activity by porins further enlarges the field of action of protein-host interactions. These proteins intervene in nonspecific host defenses (4,9,29) and, as a consequence, in the specific immunologic response (27). Among surface components, therefore, porins can be considered another surface molecule, in addition to LPS, that may be an important inducer of biological activity in interactions with the host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence of proinflammatory activity by porins further enlarges the field of action of protein-host interactions. These proteins intervene in nonspecific host defenses (4,9,29) and, as a consequence, in the specific immunologic response (27). Among surface components, therefore, porins can be considered another surface molecule, in addition to LPS, that may be an important inducer of biological activity in interactions with the host.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins, therefore, induce the activation of the complement system by acting both on the classic pathway and on the alternative pathway (9); they bind to human polymorphonuclear leukocytes, decreasing some of their biological functions (29), and act as mitogens for B lymphocytes (24,27). Furthermore, in rats the porins increase the toxicity of cardiotoxic molecules (8) and damage renal tubules (28).…”
mentioning
confidence: 99%
“…Porins of Salmonella typhimurium have endotoxin-like e¡ects such as lethal action, the ability to elicit a local Shwartzman reaction and pyrogenicity [10]. S. typhimurium porins also activate the complement system in vitro and in vivo [11]. Furthermore, the porins have the ability to stimulate pro-and anti-in£ammatory cytokine synthesis and release [12^14].…”
Section: Introductionmentioning
confidence: 99%
“…Several workers have demonstrated porins to be important antigens, which elicit CMI responses through a delayed-type hypersensitivity reaction, interleukin-2 (IL-2) and interferon-g (IFN-g) production, and mitogenic effects on T and B cells [4,10]. Porins also activate the complement system and contribute to the pathogenesis of the bacterial infection [11,12]. Recently, we have demonstrated that significant lymphoproliferation could be obtained by immunization with porins.…”
Section: Introductionmentioning
confidence: 99%